2014
DOI: 10.1038/npp.2014.85
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hormone Exposure Reduces mGluR5 Expression in the Nucleus Accumbens: Functional Implications for Interoceptive Sensitivity to Alcohol

Abstract: Escalations in alcohol drinking associated with experiencing stressful life events and chronic life stressors may be related to altered sensitivity to the interoceptive/subjective effects of alcohol. Indeed, through the use of drug discrimination methods, rats show decreased sensitivity to the discriminative stimulus (interoceptive) effects of alcohol following exposure to the stress hormone corticosterone (CORT). This exposure produces heightened elevations in plasma CORT levels (eg, as may be experienced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 78 publications
6
44
0
Order By: Relevance
“…The processes driving these adaptations need to be examined. Preclinical studies indicate that acute administration of corticosterone (27) and acute stress-induced increases in corticosterone (28) reduce the expression of mGluR5. However, PTSD seems to be associated with down-regulation of the glucocorticoid-related gene serum-and glucocorticoidregulated kinase 1 (SGK1) (29) and now, FKBP5.…”
Section: Discussionmentioning
confidence: 99%
“…The processes driving these adaptations need to be examined. Preclinical studies indicate that acute administration of corticosterone (27) and acute stress-induced increases in corticosterone (28) reduce the expression of mGluR5. However, PTSD seems to be associated with down-regulation of the glucocorticoid-related gene serum-and glucocorticoidregulated kinase 1 (SGK1) (29) and now, FKBP5.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were trained using the same behavioral chambers and procedures as previous studies from this laboratory (Besheer et al 2012; Besheer et al 2014; Besheer et al 2009). Briefly, immediately following intragastric gavage (IG) administration of alcohol (1 g/kg) or water rats were placed in the chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Daily training sessions (Monday–Friday) were conducted as we previously described (Besheer et al, 2012, 2014; Cannady et al, 2011). Briefly, alcohol (1 g/kg) or water was administered IG and immediately afterward, rats were placed in the chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Discriminative stimulus (interoceptive) effects of drugs are commonly indexed using drug discrimination procedures in both humans and animals. Using these procedures, we have demonstrated that following a 7-day period of exposure to the stress hormone CORT, rats show decreased sensitivity to the discriminative stimulus effects of both experimenter- and self-administered alcohol (e.g., decreased alcohol-appropriate responses; Besheer, Fisher, Grondin, Cannady, & Hodge, 2012; Besheer, Fisher, Jaramillo, Frisbee, & Cannady, 2014). Additionally, these CORT-induced behavioral adaptations are suggested to be related, in part, to glutamatergic neuroadaptations, and functional involvement of the Group I metabotropic glutamate receptor subtype 5 (mGluR5) has been determined (Besheer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation